Education Attainment in Brazil The Experience of FUNDEF - de Mello, Luiz (OECD Economics Department Working Papers, 2005)
For many years, Brazil lagged behind other middle-income countries in terms of school enrolment rates. But since 1998 policies have aimed at bridging this gap, in particular, with the implementation of FUNDEF, a fund for financing sub-national spending on primary and lower-secondary education. Using state- and municipality-level data during 1991-2002, this paper shows that FUNDEF played a key role in the increase in enrolment rates over the period, particularly in small municipalities, which rely more heavily on transfers from higher levels of government as a source of revenue. These findings underscore the importance of FUNDEF in eliminating supply constraints to the improvement of education attainment. Enrolment rates are now nearly universal for primary and lower-secondary education. Emphasis should therefore be placed on policies to improve the quality of services and to remove supply constraints to the expansion of enrolment in upper-secondary and tertiary education